GERAKAN LITERASI SEKOLAH: TANTANGAN LITERASI DI ERA DIGITAL DAN CARA MENGATASINYA - Parentah Lubis; Mardianto Mardianto; Muhammad Irwan Padli Nasution (Jurnal Media Infotama, 2023)
In this article, we will explore the concept of the school literacy movement as well as the literacy challenges in the digital age that need to be addressed. In addition, we will describe several effective ways to overcome these challenges in order to create a literacy environment that is inclusive, adaptive and responsive to technological developments. By understanding the challenges of literacy in the digital era and implementing appropriate strategies, the School Literacy Movement can become a driving force that encourages the progress of student literacy in this digital era. The method used in this research is qualitative method. The purpose of this research is to provide an understanding of literacy challenges in the digital era and how to overcome them in the context of the School Literacy Movement. The data sources for this study come from books, journals and reading materials that are relevant to the discussion in this study.